Halogen⋯halogen interactions in diiodo-xylenes. Issue 7 (3rd January 2017) - Albright, Emily; Cann, Jonathan; Decken, Andreas; Eisler, Sara
Abstract : Iodine interactions were investigated in a series of diiodo-xylene isomers. I⋯I and other noncovalent halogen bonds were found to play a critical role in defining the solid-state structures of these compounds. Abstract : Four isomers of diiodo-xylene were synthesized and their single crystal X-ray structures determined. I⋯I interactions were found to play a strong role in defining the crystal packing patterns of these simple aromatic structures.